E-COMMERCE AND ECONOMIC GROWTH IN INDONESIA: ANALYSIS OF PANEL DATA REGRESSION - Kandi Dwi Pratiwi (GEMA PUBLICA, 2022)
Digital economy has a major contribution to Indonesia's Gross Domestic Product (GDP). Digital economy sector that has the highest growth is e-commerce. The development of e-commerce and rapid improvements in internet infrastructure are expected to encourage public consumption, so as to increase GDP growth. The purpose of the research examines the general overview of economic growth and several e-commerce indicators in Indonesia and analyzes the effect of several e-commerce indicators on economic growth in Indonesia from 2016 to 2018. Economic growth and several e-commerce indicators in Indonesia have a positive trend. DKI Jakarta has some of the highest e-commerce indicators compared to other provinces, while East Nusa Tenggara has the biggest number of additional points internet access locations from 2016 to 2018. The results of panel data regression analysis show that the variable computer users, e-commerce users, internet access, and expenditure on information technology communication have a positive and significant effect on economic growth in Indonesia and the e-commerce indicators that have the greatest influence is computer users. Thus, the results of this study indicate the importance of utilizing the role of e-commerce in promoting economic growth in Indonesia. Keywords: economic growth; e-commerce; panel